2022
DOI: 10.17268/sci.agropecu.2022.019
|View full text |Cite
|
Sign up to set email alerts
|

Quinoa (Chenopodium quinoa): Nutritional composition and bioactive compounds of grain and leaf, and impact of heat treatment and germination

Abstract: Quinoa (Chenopodium quinoa) is an Andean pseudocereal produced in countries such as Bolivia, Peru, Ecuador and southern Colombia, with more than 3,000 varieties, distinguished by their nutritional properties and adaptation to different agro-ecological zones. Quinoa's nutritional profile stands out for its protein, carbohydrate, lipid and gluten-free content; it is rich in vitamins; and it is an excellent source of minerals, such as calcium, magnesium, iron and phosphorus. It is one of the few foods that have i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 67 publications
1
4
0
Order By: Relevance
“…In comparison to WF, SQF and SKF exhibited lower starch content, and higher TDF, IDF, protein, fat, ash (minerals), and PA were observed for (p < 0.05, Table 1), consistent with findings from previous studies [21][22][23]. In general, all analyzed minerals were present in significantly higher concentrations in SQF and SKF compared to WF, except for iron (Fe), which was found in slightly lower concentration in SQF compared to WF, in consistency with observations reported for iron content in quinoa and wheat grains in the review by Campos-Rodríguez et al [24]. Data are means ± standard deviation (n = 2).…”
Section: Nutritional Quality Of Sqf Skf and Cuf Is Remarkably Higher ...supporting
confidence: 91%
“…In comparison to WF, SQF and SKF exhibited lower starch content, and higher TDF, IDF, protein, fat, ash (minerals), and PA were observed for (p < 0.05, Table 1), consistent with findings from previous studies [21][22][23]. In general, all analyzed minerals were present in significantly higher concentrations in SQF and SKF compared to WF, except for iron (Fe), which was found in slightly lower concentration in SQF compared to WF, in consistency with observations reported for iron content in quinoa and wheat grains in the review by Campos-Rodríguez et al [24]. Data are means ± standard deviation (n = 2).…”
Section: Nutritional Quality Of Sqf Skf and Cuf Is Remarkably Higher ...supporting
confidence: 91%
“…Research focused on gene expression and regulation includes hybridization (Hodková & Mandák, 2018), phylogenetic (Li et al, 2022), and proteomic studies in relation to edaphoclimatic factors where cultivars are grown (Zhao et al, 2022). The main objective of genic expression studies has been to find the relationship between the agri-environmental offer and the genetic variability associated with the greater production of seeds with high contents of vegetable proteins (El-Hakim et al, 2022) and high-value biocomposites (Campos-Rodriguez et al, 2022). This is consistent with what was reported by and García-Parra, Zurita-Silva, et al (2020), who indicated that the environmental temperature plays an important role in the phenological phases prior to the development of the seed, influencing productive and compositional aspects.…”
Section: Green Cluster (89 Key Topics)-genic Expressionmentioning
confidence: 99%
“…In terms of its essential amino acid composition, quinoa stands out for its high lysine content and a very complete amino acid profile (18,19). Most cereals are deficient in essential amino acids such as threonine, lysine, and tryptophan (20).Table 1 describes the amino acid profile of some pseudocereals, showing that quinoa has a high content of arginine (14.0 g/100 g of protein), proline (9.4 g/100 g of protein), and lysine (6.9 g/100 g of protein) compared to other pseudocereals. Furthermore, the lysine content exceeds the FAO/WHO recommended value (5.5 g/100 g of protein) (21,22).…”
Section: Nutritional and Functional Properties Of Quinoamentioning
confidence: 99%